How to imagine an inclusive post-Covid university education - Antonella Valenti; Lorena Montesano; Alessandra M. Straniero (Firenze University Press, 2021)
This paper aims to analyse the criticalities and strengths of distance learning provided during this period of health emergency, by analysing the opinions of university students with disabilities and SLD. Specifically, we present the results of an ad hoc questionnaire administered to the students with disabilities and Specific Learning Disability (SLD) enrolled at the University of Calabria. Through this, we aimed to provide important insights, to be taken into account in the future, especially in view of the re-arrangement of the University's teaching activities. Furthermore, we intended to highlight how universal design in the educational field should constitute a widespread and systematic working method for the creation of truly inclusive learning and relationship environments, also at a distance.   Come immaginare una didattica universitaria post-Covid inclusiva.   Il presente contributo si pone l'obiettivo di analizzare le criticità e i punti di forza della didattica a distanza (DaD) erogata durante questo periodo di emergenza sanitaria, analizzando le opinioni degli studenti e delle studentesse con disabilità e Disturbi Specifici dell'Apprendimento (DSA). In particolare, si presentano i risultati ottenuti tramite la somministrazione di un questionario ad hoc agli studenti e alle studentesse con disabilità e DSA iscritti presso l'Università della Calabria. In tal modo si auspica di fornire utili spunti di riflessione, dei quali tener conto in futuro, soprattutto in vista di una riorganizzazione delle attività didattiche dell'Ateneo. Si tenterà, inoltre, di mettere in luce come la progettazione universale in campo educativo debba costituire una modalità di lavoro diffusa e sistematica per la creazione di ambienti di apprendimento e relazione davvero inclusivi, anche a distanza.